Struktura i uwarunkowania afektywne go komponentu postaw politycznych studentów - Pawełczyk, Piotr; Churska-Nowak, Karolina; Jankowiak, Barbara (Przegląd Politologiczny, 2018)
It is indisputable that emotions predominate in shaping political attitudes. This is corroborated by the development of political marketing, whose techniques and means are mainly directed at voters’ emotions. The paper presents the results of research into the affective component in the political attitudes of university students. To a large extent the analysis confirms the hypothesis that religious organizations have a significant impact on developing a positive emotional attitude towards right-wing politicians and parties, whereas the media strongly influence the emergence of similar attitudes towards liberal political entities. Advocates of the right wing declare their commitment to national values and patriotism, while demonstrating a relatively passive attitude to politics. The respondents whose opinions indicate liberal sympathies emphasize their satisfaction with life and intention to be active in the field of politics. The important conclusion to be drawn from this research is that the family contin- ues to have a significant impact on the emotional political attachments of the young, whereas the influence of school in this regard is definitely limited.